Trends in using of antihypertensive medication among US CKD adults, NHANES 2001–2018 - Li, Fanghua; Sun, Anbang; Wu, Feng; Zhang, Dongshan; Zhao, Zhanzheng (Frontiers in Cardiovascular Medicine, 2023)
Objective: Blood pressure (BP) control rates among adult patients taking antihypertensive medications in the United States have not improved over the last decade. Many CKD adults require more than one class of antihypertensive agent to reach the BP target recommended by the guidelines. However, no study has quantified the proportion of adult CKD patients taking antihypertensive medication who are on monotherapy or combination therapy. Methods: National Health and Nutrition Examination Survey data during 2001-2018 was used, including adults with CKD taking antihypertensive medication (age ≥20 years, n=4,453). BP control rates were investigated under the BP targets recommended by the 2021 KDIGO, the 2012 KDIGO, and the 2017 ACC/AHA guidelines. Result: The percentages of uncontrolled BP among US adults with CKD taking antihypertensive medication were 81.4% in 2001-2006 and 78.2% in 2013-2018. The proportion of monotherapy of antihypertensive regimen were 38.6%, 33.3%, and 34.6% from 2001-2006, 2007-2012, and 2013-2018, with no obvious difference. Similarly, there was no significant change in percentages of dual-therapy, triple-therapy, and quadruple-therapy. Although proportion of CKD adults not treated with ACEi/ARB decreased from 43.5% in 2001-2006 to 32.7% in 2013-2018, treatment of ACEi/ARB among patients with ACR >300 mg/g had no significant change. Conclusion: The BP control rates among US adult CKD patients taking antihypertensive medications have not improved from 2001 to 2018. Mono-therapy accounted for about one third of adult CKD patients taking antihypertensive medication and not changed. Increasing antihypertensive medication combination therapy may help improve BP control in CKD adults in the United States.